The Influence of Thrombocytopenia in Covid-19 Patients on Dengue Hemorrhagic Fever Cases - Kadek Lia; Onny Setiani; M Sakundarno Adi (Utan Kayu Publishing, 2023)
The increasing cases of Dengue Hemorrhagic Fever in all regions of Indonesia are a disease transmitted through a vector amid the ongoing COVID-19 Pandemic, which can seriously threaten public health. This study aims to analyze the relationship between thrombocytopenia in patients with COVID-19 and cases of dengue hemorrhagic fever. This research was conducted from February to March 2022. The tools used in this study were the Abbot Cell-Dyn Ruby Hematology Autoanalyzer and questionnaires as well as PCR secondary data. Anas used Pearson's Correlation Test statistic and used a cross-sectional study design with 389 respondents who came to check blood at the laboratory. Based on the data obtained, 128 respondents had thrombocytopenia (32.9%) diagnosed with Dengue Hemorrhagic Fever, and as many as 70 out of 128 respondents had been exposed to COVID-19 (54.7%). The analysis results show a relationship between the influence of thrombocytopenia in patients with COVID-19 and cases of Dengue Hemorrhagic Fever. It is necessary to improve anamnesis in patients suspected of Dengue Hemorrhagic Fever, it is hoped that they will carry out investigations related to previous exposure to COVID-19, so that they can provide, fast, precise and accurate treatment and treatment.